Reproductive efficiency of Nellore cows nursing Nellore or crossbred Simmental x Nellore calves - Vargas Júnior, Fernando Miranda de; Wechsler, Francisco Stefano [UNESP]; Oliveira, Marcus Vinicius Morais de; Seno, Leonardo de Oliveira [UNESP]; Fernandes, Alexandre Rodrigo Mendes [UNESP]; Camilo, Fernando Rossi [UNESP] (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2013)
The objective of this study was to analyze the influence of genetic group (GG) of the calf during gestation, mobilization of body reserves and period of postpartum anestrus in Nellore cows. Thirty-seven primiparous and multiparous cows were used: 24 gave birth to Nellore (NEL), and 13 gave birth to 1/2 Simmental x 1/2 Nellore (SIM) calves. According to the date of calving, cows were divided into three blocks, with intervals of 20 days between blocks. The body condition (BC) of the cows was estimated subjectively on a scale from 0 to 5 points, with intermediate grading of 0.5 points. We measured the thickness of subcutaneous fat (SF) between the 12th and 13th ribs and rump by ultrasound. Blood samples from each cow were collected weekly from the third week after birth until weaning, to analyze the level of progesterone; in the samples collected until 16 weeks postpartum, we analyzed the concentration of nonesterified fatty acids(NEFA). The gestation period of mothers of NEL calves was eight days longer, on average. The variables relating to the mobilization of body reserves (NEFA, BC and SF) were not influenced by calf GG, with the only significant effects being the number of days postpartum, witha peak in the concentration of NEFA between the sixth and eighth weeks and linear decrease in BC and NF. Mothers of NEL calves remained in anestrus for 4.6 weeks longer than the mothers of crossbred calves.
Keywords: Anestrus; Body condition; Crossing; Subcutaneous fat